Self-sensing ultra-lightweight engineered cementitious composites (ECC) with carbon fibres - Ran, Hongyu; Elchalakani, Mohamed; Hu, Zhiheng; Yehia, Sherif; Ali Sadakkathulla, Mohamed; Guo, Xiao (Measurement : journal of the International Measurement Confederation, 2024)
•Self-sensing ULW-ECCs with seven CF lengths were developed.•The density of smart ULW-ECC fell within the range of 1000–1200 kg/m3.•The inclusion of CF improved the self-sensing performance of ULW-ECC, especially during the tensile strain-hardening stage.•It is recommended to utilize CF lengths within the range of 9–12 mm. This research introduces self-sensing ultra-lightweight engineered cementitious composites (ULW-ECCs) by hybridizing polyethylene fibre and carbon fibres (CF) designed for structural health monitoring and retrofitting applications. The investigation explores the self-sensing performance and electrical conductivity of smart ULW-ECC with seven CF lengths ranging from 1 to 20 mm. Initially, mechanical properties and electrical conductivity were assessed, followed by the impact of temperature and water content in composite on electrical conductivity. The self-sensing capability under both tension and flexure was examined, complemented by a scanning electron microscope (SEM) test. The density of smart ULW-ECC fell within the range of 1000–1200 kg/m3 under the compressive strength of about 30 MPa. The integration of CF enhanced the compressive and flexural strength while reducing the tensile strain capacity. The electrical conductivity of the specimen with CF initially raised and then slightly declined with CF length from 1 to 20 mm, with the highest conductivity observed at 12 mm. Incorporating CF could diminish the influence of the environment on the electrical conductivity of ULW-ECC. Furthermore, the inclusion of CF improved the self-sensing performance of ULW-ECC, especially during the tensile strain-hardening (multiple microcracking) stage, although this efficacy was subject to variation based on CF length. Considering the mechanical, self-sensing, and conductive properties, it is recommended to utilize CF lengths within the range of 9–12 mm. This work confirms that CF-reinforced ULW-ECC could achieve excellent mechanical properties and self-sensing ability.